Innovator-firm collaboration: the moderating role of transactional capacity (TC) - Abdul Hamid, Norhadilah; Abd Rahman, Azmawani; Ahmad, Md. Fauzi; Ahmad, Ahmad Nur Aizat (ExcelingTech, 2018)
Product innovation’s success at research and development level, does not guarantee that it will lead to the success in commercialization stage. Despite the enormous research efforts, the commercialization rates of product innovation are still at an alarming level in many countries including Malaysia. While collaboration has been acknowledged as pertinent to the success of innovation product commercialization, the collaborative effort between innovation recipient firm and the innovators remains limited. Besides, one of the central questions is how and under what condition the two parties are more likely to engage in a resilient collaborative effort, from the perspective of innovation recipient firms remain unclear. This new perspective requires an understanding of the relationship between collaboration and commercialization performance and the moderating effect of TC from firm’s perspective. Based on the response of 104 product innovation recipient firms, the findings show that collaboration positively affects firm’s market performance and innovation survival. In addition, transactional capacity gives medium effect to collaboration, leading to better firm’s innovation survival. This study contributes to the literature by exploring how close collaboration between firm and innovator initiates to enhance the firm’s market performance and innovation survival. It also increases our understanding of how TC relate to collaboration and market performance and innovation survival.